Management of behavioural symptoms of dementia in a specialized unit care. Issue 2 (8th February 2016) - Saidlitz, Pascal; Sourdet, Sandrine; Voisin, Thierry; Vellas, Bruno
Abstract: Background: In France, the Alzheimer Plan 2008–2012 has enabled the development of units specialized in managing the behavioural and psychological disorders found in cognitive pathologies, with an emphasis on both pharmacological and non‐pharmacological treatments. The aim of this study was to analyze the evolution of behavioural symptoms, autonomy, and psychotropic drug prescriptions at a cognitive and behavioural unit in Toulouse, France. Methods: Prospective study, with systematic analyze of data for patients hospitalized in a cognitive and behavioral unit. Results: This 2‐year study included 199 patients. Behavioural symptoms were significantly improved during the follow‐up period and remained so after discharge. Autonomy, especially in walking, was not altered. The prescription of psychotropic drugs, such as neuroleptics, was significantly lower at discharge. Conclusion: This study showed the effectiveness of overall care, with an emphasis on pharmacological and non‐pharmacological treatments, in managing disruptive behavioural symptoms in a specialized unit.